The jewel and the stone - Eskinazi, Lucas (Revista do Colóquio, 2026)
An essay developed from the intersection of literature, photography, and reflections on life. Beginning with a brief text in which I recount the cosmological thoughts of a friend, I seek to engage with these ideas through a set of images produced in the ongoing practice of photographing in the city. I have been observing trees and their formal expressions in the urban context, and it may be possible to trace a continuity in their representation across different visual forms, in this way centered, as the protagonists of the image.